Clinical Effectiveness of Liraglutide vs Sitagliptin on Glycemic Control and Body Weight in Patients with Type 2 Diabetes: A Retrospective Assessment in Sweden. Issue 2 (June 2016) - Lind, Marcus; Matsson, Per-Olov; Linder, Ragnar; Svenningsson, Irene; Jørgensen, Leif; Ploug, Uffe; Gydesen, Helge; Dorkhan, Mozhgan; Larsen, Sara; Johansson, Gunnar
Abstract Introduction The aim of the present study was to use real-world data from Swedish primary-care and national registries to understand clinical outcomes in patients with Type 2 diabetes (T2D) treated with liraglutide in clinical practice, and to compare with data from those treated with sitagliptin. Methods This was a non-interventional, retrospective study conducted between February 2014 and September 2014 using T2D patient data from Swedish primary-care centers and national healthcare registries. The primary objective was to assess the effectiveness of liraglutide in control of glycemia and body weight in clinical practice (stage 1). The secondary objective was to compare the clinical effectiveness of liraglutide with sitagliptin on glycemic control and body weight in clinical practice in a propensity-score-matched population (stage 2). Results In stage 1 (n = 402), 39.4% of patients treated with liraglutide achieved ≥1.0% (10.9 mmol/mol) reduction in glycated hemoglobin (HbA1c) after 180 days of treatment and 54.9% achieved the target HbA1c of <7.0% (53.0 mmol/mol). Moreover, compared with baseline, 22.5% of patients treated with liraglutide achieved both ≥1.0% reduction in HbA1c and ≥3.0% reduction in body weight. In stage 2, a significantly greater proportion of patients receiving liraglutide (n = 180) than sitagliptin (n = 208) achieved ≥1.0% reduction in HbA1c [52.9% vs 33.5%, respectively (P = 0.0002)]. Mean body-weight loss was also significantly greater in patients receiving liraglutide vs sitagliptin [−3.5 vs −1.3 kg, respectively (P < 0.0001)]. Conclusion This study provides real-world evidence from Sweden corroborating previous clinical trials that demonstrate greater efficacy of liraglutide over sitagliptin on glycemic control and body-weight reduction in patients with T2D. Funding Novo Nordisk A/S. Trial registration ClinicalTrials.gov identifier NCT02077946.